Determinants of My Rentokil Reporting System Adoption and its Impact on Employees’ Job Satisfaction - Lutfhi Chairul Alam; Nur Budi Mulyono (Publikasi Indonesia, 2026)
The adoption of reporting systems in organizations does not always lead to consistent use, especially in systems that are already in the post-adoption stage and integrated into routine work activities. MyRentokil is implemented at PT Rentokil Initial Indonesia to support service reporting and operational control; however, variations in employee usage behavior are still observed. This research aims to analyze the determinants of the adoption of the MyRentokil reporting system and its impact on employee job satisfaction. This quantitative study surveyed internal users (technicians and service supervisors) at PT Rentokil Initial Indonesia’s Tangerang branch and analyzed the data using PLS-SEM based on the UTAUT2 framework. The results of the study showed that business expectations had a significant effect on behavioral intention, while performance expectations did not have a significant effect. Behavioral intention also did not have a significant effect on actual usage behavior, indicating a gap between intention and usage in the context of organizational systems that have been integrated into work activities. Conversely, supportive conditions and habits were found to be the main factors influencing usage behavior. In addition, system usage behavior had a positive and significant effect on employee job satisfaction. In mature systems, sustained use depends more on ease of use, organizational support, and work habits than on perceived performance benefits or usage intention. This study extends the UTAUT2 framework to post-adoption contexts, offering practical insights for strengthening system use through structural integration to enhance job satisfaction.